Renewal of Criminal Provisions in the Employment Cluster Job Creation Law - Ratih Damayanti; Muhammad Azil Maskur; Ahmad Gelora Mahardika; Putri Balqis Nuril Hakim; Masyhar, Ali; Rodiyah, Rodiyah (Indonesian State Law Review, 2025)
This study aims to analyze the reform of criminal provisions in the Job Creation Law concerning labor. The amendments, which eliminate and modify criminal provisions, raise concerns about the potential erosion of legal enforcement regarding labor rights violations. This research employs a normative legal approach, focusing on conceptual frameworks and legislative regulations. Data were collected through literature review from primary legal sources, including relevant labor laws, and secondary sources such as legal books and journals. The findings indicate that while the reform of criminal provisions has positive impacts, it also presents negative consequences due to the regulation of these provisions outside the labor law framework. This duality underscores the need for careful consideration in balancing legal protections for workers with the objectives of efficient law enforcement in the evolving labor landscape.